Study of membrane-binding and membrane-insertion mechanisms of Listeriolysin O, a prominent member in the cholesterol-dependent cytolysin family of -barrel pore-forming toxins - Kusum Lata (My University, 2025)
Listeriolysin O (LLO) is a prominent member in the family of cholesterol-dependent cytolysins (CDCs), and a crucial virulence factor secreted by Listeria monocytogenes. The pore-forming activity of LLO is vital for the pathogenesis of L. monocytogenes. The pore-formation mechanism of LLO, like that of other CDCs, is dependent on membrane cholesterol. It involves a series of complex conformational reorganizations, making the mechanism challenging to fully comprehend. The present study has explored the mechanistic basis of LLO binding to the membrane, and the membrane-insertion of its pore-forming motif to form the functional pores. In the first part of the study, we have investigated the roles of cholesterol in facilitating LLO activity and examined the mechanistic basis of the LLO-cholesterol interaction. Here, we show that cholesterol promotes both membrane binding and oligomerization of LLO. Furthermore, the binding of LLO is dependent on the membrane composition and dynamics, particularly in cholesterol-deficient membranes. To understand the mechanistic basis of LLO-cholesterol interactions, we employed an LLO variant in which the cholesterol-recognition motif was altered (LLOT515G-L516G). Interestingly, we find that the membrane-binding and pore-forming abilities of LLOT515G-L516G, but not those of LLO, correlate with the cholesterol-dependent ordering of the lipid bilayer. Our data further suggest that the line tension arising from the lipid phase heterogeneity of cholesterol-containing membranes could play a pivotal role in LLO function, particularly in the absence of CRM-mediated cholesterol binding. Therefore, in addition to its receptor-like role, we conclude that cholesterol further facilitates the pore-forming and membrane-damaging functionality of LLO by establishing the optimal physicochemical environment in the membranes. In the second part of this study, we have explored the structural and functional significance of the two transmembrane helices (TMHs), TMH1 and TMH2, in LLO pore-formation. We have observed that both TMH1 and TMH2 play crucial roles in maintaining the structural integrity of the LLO monomer. Additionally, we have found that the membrane-insertion processes of the two TMHs follow distinct kinetics, yet they are strictly interdependent. Furthermore, we have examined the roles of the aromatic residues within the TMHs in the pore-formation mechanism of LLO. Overall, the findings from our study offer crucial new insights into the molecular mechanisms governing the membrane-binding and insertion mechanisms of LLO, thus contributing to the broader and more detailed understanding of the mechanism of CDC pore-formation processes.
Keywords: Listeriolysin O